Kedudukan Hukum Hasil Rapat Anggota Tahunan Sebagai Dasar Dalam Menjalankan Kegiatan Usaha Koperasi (Studi Pada Kantor Koperasi Karya Bahari Lombok Utara) - M Mulyawan (Universitas Medan Area, 2023)
This study aims to determine the legal standing of the results of the Annual Member Meeting as a basis for carrying out cooperative business activities (study at the Karya Bahari Cooperative Office, North Lombok)